Partial Fuzzy Soft Metric Space - Younes Hazem Thiyab; Ghaith Ali Salom (Journal of Applied Science and Engineering)
Matthew introduced a partial metric, sometimes known as a non-zero self-distance. This paper seeks to extend Matthew’s notion to the fuzzy soft universe and create a partial fuzzy soft metric. Then we investigate the convergence of fuzzy soft sequences, fuzzy soft closed ball, fuzzy soft open ball, fuzzy soft map, and fuzzy soft fixed point theorems in a partial fuzzy soft metric space, as well as some fundamental characteristics.